DARI MITOS TUJUH PUTRI HINGGA LEGITIMASI AGAMA: SUMBER KEKUASAAN SULTAN TERNATE - Rustam Hasyim (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2017)
Noble people from the circle of Sultanate of Ternate construct and maintain their power base by creating the magical aspect of religious and Culture. This hegemonic strategy allowed this group to pose a certain powerful position and to have a certain place in the heart of the people of Ternate. There are, at least, four important heritage elements in the Sultanate of Ternate used as a strategy to form and strengthen their position. The first is the doctrine Jou se Ngofangare (king and servant) which means Sultan as the representation of God's power (macro cosmos). Second is the mythical Seven Princess, which justifies the Sultan position by using magical-religious as a means to gain people consent. Third, this group tends to use their noble title and heirloom as signs of charisma and sacred magical power. Those heirlooms such as sword and title function to legitimize the Sultan as ruler. Fourth, Kadaton (palace) which produces cultural meaning as the highest indigenous identity and the source of magical belief